Developing Campus-Community Based on Waste Management: Learning from Universitas Muhammadiyah Malang - Rachmad Kristiono Dwi Susilo; Ahmad Mujahid Arrozy; Soewignyo Soewignyo (Jurnal Studi Sosial dan Politik, 2022)
Using a campus community-based participation approach makes local choices more revealing and we use this approach to create a reflection on local views relatively but recorded on a field record. The results showed that the affordable aspect of waste removal practices is considered more effective than centralized management and rigid waste sorting. This study focuses on community-based waste management practices based on academic community relations as campus-community at Campus Tiga Universitas Muhammadiyah Malang (UMM) Tlogomas Malang Regency, East Java, Indonesia. In the community-development analysis Ife and Tesoriero (2006) which began from the integrity phase of the process that removing waste in its place is still the responsibility of individuals and a culture of shame among peer-group colleagues. Then in increasing awareness it takes knowledge that removing waste needs to be based on the category of waste, it is useful for the processing of waste that is the same character of the material so that the waste processing process has the right output and conducive to environmental conditions. The phase of the cooperation model is still based on providing wages to the team or waste processing personnel with Integrated Landfill (TPS) Mulyoagung, Dau, Kabupaten Malang. Then the development step is the processing of organic waste or called "sampah dapur" which still requires a waste treatment plant strategy, waste processing machine tools and the role of human resources as community actors.